What’s in a message: A systemic functional analysis of cancer prevention messages - Collin, Jerome; Ting, Su Hie (John Wiley & Sons Ltd, 2021)
This article provides some insights on how a particular reading from a theoretical framework can bring out details and problems with health communication posters. Using Michael Halliday’s Systemic Functional Linguistics (SFL) framework, the article examines cancer prevention messages in cancer posters produced by the Ministry of Health Malaysia. The analysis shows that the posters organize and convey their intended messages through the realization of the three strands of meaning or metafunctions —the ideational, the interpersonal, and the textual—by drawing on t he grammatical resources of the language used. Such meanings are created and expressed throughout the three main sections of the posters; the heading, the body of the text, and t he signature line. Despite its practical limitations in particular linguistic contexts, the article shows that SFL is a useful tool for the analysis of Malaysia’s cancer posters and how it can potentially provide a more nuanced understanding of the country’s ongoing health risk communication initiatives.